Vicarious Liability In Corporate Crime Cases Against Environmental Crimes In The Forestry Sector - Fitri Anugrah; Topo Santoso (Journal Research of Social Science, Economics, and Management, 2022)
The concept of principle of error is born of the concept of no criminal without error (geen straf zonder schuld beginsel). A person will be held accountable for his unlawful actions. Vicarious liability is the legal responsibility of one person for the wrongful acts of another. In this study, the author used a type of normative legal research, namely research that uses secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials as the main data. Based on the case examined in the judgment No. 927 K/Pid.Sus-LH/2021 Defendant PT. NATURAL PERSADA MANDIRI has committed a criminal act of environmental corporation in the field of forestry and is obliged to carry out criminal liability represented by Nico Fernandus Sinaga as the management/director of the company imposed a fine as stipulated in Article 89 Paragraph (2) letter a juncto Article 17 Paragraph (1) letter b of Law Number 18 of 2013 concerning Prevention and Eradication of Forest Destruction.